Changes in Wage Rates Between 1959 and 1967 - Hurd, Michael D. (The Review of Economics and Statistics, 1971)
DESPITE the importance of wage rates in our understanding of economic activity, there are almost no wage data available appropriate for studying changes in the wages received by different race, sex, age, and education groups in the labor force. The only official data on hourly wages, those published in Employment and Earnings, are disaggregated by industry, but not by the personal characteristics of the wage-earners. Data on annual incomes and earnings by personal characteristics are available from the Current Population Survey, but they are not suitable for the calculation of hourly wage rates. As a result of this substantial defect in the wage statistics of the Federal Government, the recent controversy about the changes in the last decade in the relative economic well-being of blacks and whites was carried out in the absence of any information about changes in their wage rates. This study uses the 1967 Survey of Economic Opportunity (SEO), a new source of data, and the 1960 Census 1/1000 Sample in a comparison of wage rates in 1959 and 1967. Estimates of wages of individuals in 1959 are obtained by making use of additional data which were unavailable to previous investigators.' Using 1967 wage rates, recorded directly in the SEO, and the improved estimates of 1959 wage rates, average wages by race and sex are found in each of the two years. The variation of individual wages by characteristics such as age, race, sex and education is then estimated in both years, so that changes in wages can be calculated when hours worked by age, race, sex and education are held constant. This gives Laspeyres and Paasche indices of wage rates. In the final part of the paper, the structure of wage rates by personal characteristics in each of the years is studied. We found that average wage rates of blacks increased considerably more than those of whites between 1959 and 1967. Part of the increase of blacks' wages can be attributed to changes in the composition of the labor force, (mainly to an increase in average education). Even when the 1959 composition is used to calculate 1967 wages, so that changes in the level of education are eliminated, blacks had substantially greater increases in wages than whites. The average wage of blacks was still much lower than that of whites in 1967. Wages differentials by education were almost the same in both years, especially for whites. Wages of older workers declined relative to those of prime-aged workers. There was no consistent pattern in the changes of wages of young workers relative to wages of 35-44-yearold workers: young white females had higher relative wages; young white males had almost the same relative wages; young black females had generally higher relative wages; wages of black males aged 18-24 increased but wages of black males aged 16-17 decreased relative to wages of prime-aged black males. In both periods wages were, in general, lower in the South and higher in the West than in the rest of the country. Relative wages in the South and West increased during the period, so that by 1967 wages in the West were substantially higher than the average nationwide wage rates.